The Effect of Microfluidization Pressure and Tocopherol Content on the Retention of Vitamin A in Oil-In-Water Emulsions - Shahin Banasaz; Ksenia Morozova; Giovanna Ferrentino; Matteo Scampicchio (Foods, 2021)
This work investigates the oxidative stability of vitamin A encapsulated in oil-in-water emulsions, which were prepared by using a microfluidizer. All emulsions were prepared with a fixed content of vitamin A (525 µM), corn oil (10%), water (90%), and whey protein (2%), but varying two main factors: the microfluidizer pressure (10, 50, 100, 200 MPa) and the amount of α-tocopherol (0, 0.25, 0.50, 1.00 mg/g). The content of vitamin A before and after the microfluidization process, and during the subsequent five weeks of storage at 40 °C were determined by HPLC-DAD. The results of the analysis of variance performed either on the data obtained before and after the microfluidization process or during the storage showed that the highest stability of vitamin A was obtained with the highest content of α-tocopherol and with an applied pressure between 100 and 200 MPa. The highest stability was explained by the smaller particle size of the resulting oil droplets. However, high pressures (200 MPa) showed a negative effect on vitamin A retention. These results could be useful for future formulations of retinoids.